A novel epoxy/electrospun PLA nanofibre composite material: Fabrication and characterisation - Dong, Yu; Mosaval, Tariq; Haroosh, Hazim (Society of Photo-Optical Instrumentation Engineers (SPIE), 2013)
Electrospun nanofibres as the potential reinforcement in manufacturing composite materials are recently attractive due to their simple fabrication process via electrospinning to produce continuous fibrous structures. This study concentrates on the development of novel epoxy composites laminated by layers of electrospun polylactic acid (PLA) nanofibre mats to evaluate their mechanical and thermal properties by means of flexural testing and differential scanning calorimetry (DSC), respectively. The moulded composite sheets were prepared at the fibre contents of 3 wt%, 5 wt% and 10 wt% using a solution casting method. The flexural moduli of composites have been shown to be increased by 50.8% and 24.0% for 5 wt% and 10 wt% fibre contents, respectively, as opposed to that of neat epoxy. This similar trend was also found for corresponding flexural strengths being increased by 31.6% and 4.8%. However, the flexural properties become worse at the fibre content of 3 wt% with decreases of flexural modulus by 36.9% and flexural strength by 22.9%. The examination of fractured surface morphology of composites using scanning electron microscopy (SEM) confirms a full penetration of cured epoxy matrix into electrospun PLA nanofibres despite some existences of typical fibrous structures/networks detected inside the large void cavities. On the other hand, the glass transition temperatures of composites have increased to 54-60°C due to the addition of electrospun fibres as compared to 50°C for that of epoxy, indicating that those fibrous networks may further restrict the intermolecular mobility of matrix for thermal effects.